Viscoelastometry guided fresh frozen plasma infusion for postpartum haemorrhage: OBS2, an observational study. (8th September 2017) - Collins, P. W.; Cannings-John, R.; Bruynseels, D.; Mallaiah, S.; Dick, J.; Elton, C.; Weeks, A.; Sanders, J.; Aawar, N.; Townson, J.; Hood, K.; Hall, J.; et al.
Abstract: Background. Postpartum haemorrhage (PPH) can be exacerbated by haemostatic failure. Based on data from trauma studies, empirical infusions of fresh frozen plasma (FFP) are often given during severe PPH if coagulation tests are unavailable. This study observed a cohort of women with moderate/severe PPH in whom FFP infusion was guided by the use of viscoelastometric point-of-care testing (VE-POCT) and clinical assessment. Methods. Women were enrolled into this observational study when blood loss was measured or suspected to be about 1000 mL. If Fibtem A5 determined by Rotem ® thromboelastometry remained >15 mm, or bleeding stopped, FFP was withheld. If Fibtem A5 was ≤15 mm and bleeding ongoing, women were randomized into an interventional study as previously reported. Clinical and laboratory outcomes were recorded. Results. The study recruited 605 women and 98% had FFP withheld. The median (25 th –75 th centile) total blood loss was 1500 (1300–2000) mL with 300 (50–545) mL occurring after enrolment. Total blood loss was >2500 mL in 40/605 (6.6%) women. RBCs were transfused in 141/605 (23.3%) patients and 11 (1.8%) received ≥4 units. At least one invasive procedure was performed in 283/605 (46.8%) women. Level 3 care was required for 10/605 (1.7%) women. No women developed clinically significant haemostatic impairment. Conclusions. Restrictive use of FFP guided by clinical assessment of bleeding and VE-POCT is feasible and did not result in clinically significant haemostatic impairment. Studies should compare the clinical and cost effectiveness of empirical FFP infusions, according to current guidelines, with targeted use of FFP based on VE-POCT. Clinical trial registration: ISRCTN46295339 (http://www.isrctn.com/ISRCTN46295339 ) (accessed July 24, 2017), EudraCT 2012-005511-11 (https://www.clinicaltrialsregister.eu/ctr-search?query=2011-005511-11 ) (accessed July 24, 2017).